1999
DOI: 10.1136/thx.54.7.576
|View full text |Cite
|
Sign up to set email alerts
|

Markers of nitric oxide metabolism in sputum and exhaled air are not increased in chronic obstructive pulmonary disease

Abstract: Background-Nitric oxide (NO) is involved in inflammation and host defence of the lung. It has been found in increased concentrations in the airways in asthmatic subjects but its levels in patients with chronic obstructive pulmonary disease (COPD) have not been investigated. A study was undertaken to determine whether markers of NO metabolism (NO in exhaled air, iNOS expression in sputum cells, and nitrite + nitrate (NO 2 -/NO 3 -) in sputum supernatant) are increased in subjects with COPD, and whether they cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 20 publications
3
68
1
1
Order By: Relevance
“…NO is an imperfect marker of eosinophilic airway inflammation, particularly in current smokers [21]. However, the present approach is supported by some evidence that exhaled NO correlates with sputum eosinophil counts in COPD [27] and that a raised exhaled NO is more closely related to a positive response to corticosteroid therapy than other clinical markers in patients with airways disease in general [28]. No significant relationship was found between baseline exhaled NO and baseline sputum eosinophil counts.…”
Section: Discussionmentioning
confidence: 59%
“…NO is an imperfect marker of eosinophilic airway inflammation, particularly in current smokers [21]. However, the present approach is supported by some evidence that exhaled NO correlates with sputum eosinophil counts in COPD [27] and that a raised exhaled NO is more closely related to a positive response to corticosteroid therapy than other clinical markers in patients with airways disease in general [28]. No significant relationship was found between baseline exhaled NO and baseline sputum eosinophil counts.…”
Section: Discussionmentioning
confidence: 59%
“…No differences were found between the groups with respect to levels of the neutrophil chemoattractant leukotriene B 4 or neutrophil elastase activity, or in the activity of one of the natural inhibitors of neutrophil elastase, secretory leukoprotease inhibitor [127]. Finally, exhaled NO levels in COPD patients are higher in exsmokers than in smokers and nonsmokers [100,120,121], although one study reported no differences [98]. Since exhaled NO is thought to reflect airway inflammation, this suggests a worsening situation.…”
Section: Chronic Bronchitis or Chronic Obstructive Pulmonary Diseasementioning
confidence: 77%
“…In addition, the percentage of natural killer cells is higher in exsmokers than in smokers [93,94]. In exhaled air, exsmokers show similar nitric oxide levels to nonsmokers, in contrast to the lower levels measured in smokers [95][96][97][98][99][100]. In sputum, interleukin (IL)-8 levels are similar in exsmokers and smokers [101], but remain higher than in nonsmokers [102,103], suggesting that proinflammatory activity might not change after smoking cessation.…”
Section: Subjects Without Chronic Respiratory Symptomsmentioning
confidence: 79%
See 1 more Smart Citation
“…The measurement is highly reproducible in normal and asthmatic subjects if careful attention is paid to technique [533]. However, conventionally measured eNO is less useful in COPD as the levels are usually normal or only slightly elevated, except during exacerbations [534][535][536][537][538]. This is likely to be due to the increase in oxidative stress, resulting in the formation of peroxynitrite and nitrate, so that nitric oxide (NO) is removed from the gaseous phase.…”
Section: Nitric Oxidementioning
confidence: 99%